Coordinating Cooperative Collection Development: A National Perspective, 1st edition - Luquire, Wilson (Routledge, 2020)
This book, first published in 1986, is a comprehensive review of American library cooperative development programs at the regional, state-wide, interstate, and national levels. The distinguished contributors offer thoughtful assessments of the challenges of effectively implementing programs and analyse the successes and limitations of these programs.